Kerangka Konseptual Hubungan Social Proof terhadap Minat Berbelanja Online - Jaya Kusuma, Muh. Ilham; Efendi, Ahmad Efendi (Study of Scientific and Behavioral Management, 2022)
Nowadays, online shopping is an activity that is consumers often do to meet their actual needs. The decision to online shopping is influenced by several things, including social proof. The purpose of this study was to develop a conceptual framework for the impact of social proof on online shopping interest.